Comparative Analysis of Test for Improving Primary Students Mathematics Literacy Skills Through Project–Based Learning - Zuhri; .Dewi, Sinta Verawati; .Zakiah, Nina; Efendi; Happy, Nurina; Yustitia, Via (MIMBAR PGSD Undiksha, 2024)
Mathematical literacy skills are very necessary to face and solve various challenges in today's life, so these abilities need to be honed from elementary school. This research aims to analyze whether the increase in the mathematical literacy skills of students taught using a project-based learning model is higher than the mathematical literacy skills of students taught using regular learning. This type of research is quasi-experimental by dividing 2 sample groups as samples that are taught through regular learning and samples taught by applying a project-based learning model. This analysis uses the t-test to compare the means of the two sample groups. The sample in this study was 26 grade 4 children at state elementary school 064967 Medan, North Sumatra. The results of this research were the increase in the mathematical literacy skills of students taught using a project-based learning model was higher than the mathematical literacy abilities of students taught using regular learning. Through project activities, students can provide a rich understanding of concepts and ideas.